Praktik Media Relations pada Pemerintahan Kota Bandung - Apriliyanti (Program Studi Hubungan Masyarakat Politeknik LP3I, 2020)
ABSTRACT The government as an institution that represents the public interest requires media channels to maintain its reputation. The purpose of writing this article is to determine the practice of media relations carried out by the city government of Bandung. In conducting this research the writer used a qualitative descriptive research method using investigative interview techniques and in-depth interviews so that they were able to describe the results of observations and analyze the data obtained in the field. After analyzing and discussing the problem, the authors conclude that the media relations practices that occur in Bandung city government tend to be too